Reduction of Postoperative Opioid Use in Oncologic Breast Surgery and The Creation of Multimodal Pain Management Guidelines and Practices - Jehangir, Abdul Mannan; Waris, Ahsan; Sultan, Umar; Khan, Rihan Aslam; Zafar, Qasim (Indus Journal of Bioscience Research, 2025)
Background: Opioid-based postoperative analgesia in oncologic breast surgery is associated with significant adverse effects and risk of dependency. Multimodal pain management protocols offer a safer alternative by integrating multiple non-opioid strategies for effective analgesia. Objective: To evaluate the impact of a structured multimodal analgesia protocol on postoperative opioid consumption, pain control, patient satisfaction, adverse effects, and hospital stay duration in breast cancer surgery patients. Methods: This prospective comparative study was conducted at Nishtar Hospital, Multan, from November 2024 to April 2025. A total of 187 female patients undergoing oncologic breast surgery were enrolled and divided into two groups: Group A (pre-implementation phase, n=94) and Group B (post-implementation phase, n=93). The intervention group received a standardized multimodal protocol including non-opioid analgesics, regional nerve blocks, and preoperative education. Results: The post-implementation group showed a significant reduction in opioid use (18.4 ± 6.5 mg vs. 48.6 ± 10.2 mg; p < 0.001) and lower VAS pain scores at all time points (p < 0.01). Patient satisfaction was notably higher, with 71.0% rating their pain management as "very satisfied" compared to 38.3% in the control group (p = 0.002). The incidence of nausea, vomiting, and sedation was significantly reduced in Group B (p < 0.01), and the average hospital stay was shorter (2.8 ± 0.7 days vs. 3.6 ± 0.9 days; p = 0.01). Conclusion: It is concluded that multimodal analgesia protocols significantly reduce opioid consumption and improve clinical and patient-reported outcomes in oncologic breast surgery. Their routine adoption is recommended as part of enhanced recovery and opioid-sparing strategies in surgical oncology.